THE INFLUENCE OF SKIMMING AND SCANNING ON STUDENT’S READING ACHIEVEMENT AT SMP TELADAN PEMATANGSIANTAR - Devita sitohang; Selviana Napitupulu (Sinar Lima, 2025)
Reading is a crucial skill in English as a foreign language (EFL) learning, as it enables students to access information, expand vocabulary, and strengthen comprehension abilities. However, many Indonesian junior high school students continue to face difficulties in understanding English texts due to limited strategy use and a tendency to read word by word. Although previous studies have shown the effectiveness of skimming and scanning techniques in improving reading comprehension, most research has focused on senior high school or university students, leaving a gap in evidence at the junior high school level, particularly in small urban contexts such as Pematangsiantar. This study aimed to examine the influence of skimming and scanning techniques on eighth-grade students’ reading achievement at SMP Teladan Pematangsiantar. A quasi-experimental design with pre-test and post-test control groups was employed, involving 60 students selected through cluster random sampling. Data were collected through a 20-item multiple-choice reading test and analyzed using descriptive statistics and an independent samples t-test. The findings showed that the experimental group achieved a higher post-test mean score (89.00) than the control group (77.00), with a significant difference confirmed by the t-test result (t-observed = 4.10 > t-table = 2.00). The results indicate that skimming and scanning techniques effectively enhance students’ reading comprehension. In conclusion, strategy-based instruction provides meaningful benefits for junior high school learners, supporting improved performance and engagement in reading Activites